CONSTRUCTION COMPANY ACCOUNTS. - Taggart, H. F. (The Accounting Review, 1926)
Abstract A number of difficulties of accounting analysis are presented by the building construction company. The kind of concern whose problems will be described enters into contracts for the erection of various types of buildings, has dealings with subcontractors, hires laborers, buys materials, makes plans and estimates on jobs contemplated, and perhaps owns a few lots and does a little building on its own account. All these activities require a precise and careful accounting, the success of which depends on a thorough understanding of the financial significance of the various operations. The principal problems have to do with the keeping of accounts with the jobs and with the customers. The proper handling of the jobs is largely a matter of cost accounting. Every job must be charged with all labor and materials, payments to subcontractors, and other costs which can be assigned to it. The customer's account in the case of a cost-plus contract is of fairly simple nature. The costs are transferred from the job account to the customer's account at appropriate times, and a further charge is made for the proper portion of the fee.